Development of Dry Permanently Induced Roller Maganetic Seperator for The Concentration of Barkin-Ladi Columbite Ore - ALABI, Oladunni Oyelola; Adeniran, Adegbola David; OTUBELU, Chukwuebuka Basil; JOSEPH, Ojotu Ijiwo; Akinbowale, Taiwo Timothy (Universitas Muhammadiyah Magelang, 2025)
The development of a permanent induced magnetic separator aims to achieve an innovative, cost-effective, and locally sustainable solution for separating columbite ore into magnetic and non-magnetic fractions. The separation of magnetic and non-magnetic ores is a critical process in various industries, including mining, recycling, resource recovery and mineral processing. The conventional methods of separation often rely on large-scale and energy-intensive equipment, making them economically prohibitive, especially for small-scale operations. Researchers and Engineers have conducted numerous studies to comprehend how different types of paramagnetic minerals behave when separated using various separator technologies. However, despite these efforts, these separators have not been widely adopted for processing different paramagnetic minerals. This paper examines the current state of these separators, providing an overview of their operational mechanisms, practical uses, and theoretical models. It goes further to develop an induced roller magnetic separator after considering various factors such as magnetic susceptibility cost and performance, while observing certain industry specifications. The resulting design was found to produce a substantial strength of the magnetic field of about 2.2 Tesla that can be used to separate certain minerals for a reasonable period of time. 2 Kg samples of the crude Barkin-Ladi columbite ore was charged into the machine hopper at 0.05 tons per hour to evaluate the effectiveness of the fabricated machine. The efficiency of the machine was found to be about 85%n. Further implementation and modification of this design will hope to yield an increase in the extraction and processing of various minerals internally within Nigeria, providing jobs and improving the economic status of the Nation.